Diabetes-induced early molecular and functional changes in aortic heart valves in a murine model of atherosclerosis. (November 2019) - Tucureanu, Monica Madalina; Filippi, Alexandru; Alexandru, Nicoleta; Ana Constantinescu, Cristina; Ciortan, Letitia; Macarie, Razvan; Vadana, Mihaela; Voicu, Geanina; Frunza, Sabina; Nistor, Dan; Simionescu, Agneta; Simionescu, Dan Teodor; et al.
Diabetes contributes directly to the development of cardiovascular aortic valve disease. There is currently no drug therapy available for a dysfunctional valve and this urges the need for additional research to identify distinctive mechanisms of cardiovascular aortic valve disease evolution. The aim of this study was to evaluate changes of valvular aortic lesions induced in a hyperlipemic ApoE −/− mouse model by early type 1 diabetes onset (at 4 and 7 days after streptozotocin induction). The haemodynamic valve parameters were evaluated by echography and blood samples and aortic valves were collected. Plasma parameters were measured, and inflammatory, remodelling and osteogenic markers were evaluated in the aortic valves. Next, correlations between all parameters were determined. The results showed early aortic valve dysfunction detected by echography after 1 week of diabetes; lesions were found in the aortic root. Moreover, increased expression of cell adhesion molecules, extracellular matrix remodelling and osteogenic markers were detected in hyperlipemic ApoE −/− diabetic mice. Significant correlations were found between tissue valve biomarkers and plasmatic and haemodynamic parameters. Our study may help to understand the mechanisms of aortic valve disease in the diabetic milieu in order to discover and validate new biomarkers of cardiovascular aortic valve disease in diabetes and reveal new possible targets for nanobiotherapies.